ANALISIS PENGARUH CORPORATE GOVERNANCE TERHADAP FINANCIAL PERFORMANCE (Studi pada Bank Umum yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021) - Muhammad Fauzan; Endang Tri Widyarti (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to analyze the effect of Corporate Governance on Financial Performance in commercial bank companies listed on the Indonesia Stock Exchange in the 2017-2021 period. This study uses ROA as the dependent variable. The independent variables used are Board size (BOD), Audit Committee (AC), Managerial Ownership (MO), Institutional Ownership (IO). This study uses secondary data obtained from annual reports of banking companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2021 period. The number of samples used were 14 banking companies after purposive sampling, so that a total of 70 observations were obtained. This study uses multiple linear regression methods with the IBM SPSS 26 program which consists of the classical assumption test, the f statistic test, the t statistic test, and the coefficient of determination test (R2). During the observation period, it shows that the data in this study have passed the classical assumption test. This indicates that the data used has met the requirements to use the multiple linear regression equation model. The results of this study indicate that Board Size (BOD) and Audit Committee (AC) do not have a significant effect on ROA. Managerial Ownership (MO) has a significant negative effect on ROA. Institutional Ownership (IO) has a significant positive effect on ROA